A model for deceased-donor transplant queue waiting times - Drekic, Steve; Stanford, David A.; Woolford, Douglas G.; McAlister, Vivian C. (Springer, 2015)
In many jurisdictions, organ allocation is done on the basis of the health status of the patient, either explicitly or implicitly. This paper presents a self-promoting priority queueing model for patient waiting times which takes into account changes in health status over time. In this model, most patients arrive as “regular” customers to the queue, but as the health of a patient degrades, their status is promoted to “priority” to reflect the increased urgency of the transplant. We model the queueing system as a level-dependent quasi-birth-and-death process, and the steady-state joint queue length distribution as well as the marginal delay distributions for each queue are computed via the use of matrix analytic techniques. The model is calibrated using liver transplantation wait-list data, provided by a regional health centre in Canada, which tracked approximately 1,100 patients over nearly 13 years. Blood-type-specific models are fit and performance measures, such as the mean and distribution of the time until transplant, are obtained and compared to empirical estimates calculated using the raw data.
The final publication is available at Springer via http://dx.doi.org/10.1007/s11134-014-9417-7
Keywords: Abandonment; Competing risks; Estimation; Liver transplantation; Phase-type distribution; Quasi-birth-and-death process; Reneging; Queuing theory; Queues and services